Introduction to ANIMAL PRIVACY: Historical and Conceptual Approaches - Klein Käfer, Natacha; Mills, Brett; Nagai, Kaori (Privacy Studies Journal, 2026)
This article introduces the special issue Animal Privacy, situating its contributions in the fields of animal studies and privacy studies. By analyzing how a focus on non-human perspectives can reframe understandings of privacy, this introduction highlights how the authors in this special issue add new perspectives on animal privacy in the context of technology and surveillance, ethics and consent, captivity and observation, colonialism and extraction, as well as the crossing and protecting of thresholds.